Studi literatur: media belajar bebasis arduino uno pada pembelajaran fisika - Rudianto, Rudianto; Annovasho, Jhelang; Mardaya, Mardaya (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
This study aims to discuss the feasibility of learning media using Arduino Uno for the last 10 years in learning Physics. The author of the article uses the library method by collecting data using the Publish or Perish application from a national journal for physics learning media over the last 10 years. Data analysis technique using content analysis. The results showed that the use of learning media using Arduino Uno as a teaching material was very widely used in physics learning. Some teaching materials that use Arduino Uno a lot include the use of temperature measuring devices using the lm35 sensor, Water Discharge Meters using Flow Sensors, Photodiode sensors, solar cells, ultrasonic sensors, light dependent resistors and so on. With the media eligibility average being in the valid and very valid categories, the average is in the vulnerable category of more than 75%. With this literature study, researchers can compare the use of Arduino Uno, which is one of the best learning media to use.